2021
DOI: 10.1016/j.jiph.2021.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations and socio-demographic status of COVID-19 patients during the second-wave of pandemic: A Bangladeshi experience

Abstract: Background Bangladesh is a densely populated country with a substandard healthcare system and a mediocre economic framework. Due to the enormous number of people who have been unaware until now, the development of COVID-19’s second-wave infection has become a severe threat. The present investigation aimed to characterize the clinical and socio-demographic characteristics of COVID-19 in Bangladesh. Methods A cross-sectional analysis was carried out from all the other COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
38
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 47 publications
9
38
0
1
Order By: Relevance
“…Fever and respiratory symptoms were most common among the patients, reported in other studies in Bangladesh and beyond. 18 24 28 While several studies from Bangladesh, 24 29 China 28 30 and Brazil 31 reported weakness or fatigue as a common symptom, only 8% (n=31 out of 377) of the patients reported that they experienced weakness during initial triage at the hospital.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fever and respiratory symptoms were most common among the patients, reported in other studies in Bangladesh and beyond. 18 24 28 While several studies from Bangladesh, 24 29 China 28 30 and Brazil 31 reported weakness or fatigue as a common symptom, only 8% (n=31 out of 377) of the patients reported that they experienced weakness during initial triage at the hospital.…”
Section: Discussionmentioning
confidence: 99%
“… 22 38 Other studies from Bangladesh also reported that antibiotics are the most commonly used medication during the treatment of COVID-19. 24 39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 114 eligible studies 2 , 3 , 4 , 5 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ,…”
Section: Tableunclassified
“…The delta variant in Bangladesh is a concern for the country because medical facilities, such as hospital beds, intensive care units (ICU), oxygen supply for critical patients, ventilators, are far fewer than the required amount in both government and private hospital 23,28 . Health experts think that the infection and death pattern of the second wave of the COVID-19 pandemic would be more severe than the first wave 29 and World Health Organization has warned about the third wave of COVID-19 30 . The case fatality rate (CFR), which is an important parameter to measure the severity of infections of a disease like COVID-19, was relatively higher among the old age population, medical professionals, and law enforcement staff during the first wave of COVID-19 in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%